Association of neonatal hypothermia with neonatal hypoglycemia - Hoermann, Henrike; Roeper, Marcia; Friesl, Lisa; Kurz, Calvin; Tautz, Juliane; Dzietko, Mark; Mayatepek, Ertan; Meissner, Thomas; Kummer, Sebastian (Frontiers in Endocrinology, 2025)
IntroductionAbout 15% of neonates suffer from hypoglycemia. Hypothermia is associated with hypoglycemia; however, there are limited empiric data analyzing this association. Accordingly, hypothermia is not listed as a risk factor in many hypoglycemia guidelines. This study aimed to analyze hypothermia in regard to neonatal hypoglycemia.MethodsProspective study of 1018 neonates ≥35 + 0 weeks. Neonates at-risk for hypoglycemia (n=857) received a standardized blood glucose (BG) screening/management. Controls (n=161) received at least two BG measurements at 2–3 and 36–72 hours. Rectal temperature was measured at 1–3 hours, upon transfer to the maternity/pediatric ward, and at clinical discretion (hypothermia = <36.5°C).Results236/1018 (23.2%) neonates had at least one episode of hypothermia. More hypothermic compared to non-hypothermic neonates had hypoglycemia ≤2.5 mmol/l (≤45 mg/dl) (53.4% vs. 26.2%, P<.001) and <1.7 mmol/l (<30 mg/dl) (12.7% vs. 1.4%, P<.001), and subsequently required treatment more frequently. Small for gestational age (SGA) and/or fetal growth restriction (FGR), prematurity and perinatal stress were associated with a higher risk for hypothermia. In SGA and/or FGR neonates the incidence of hypoglycemia ≤2.5 mmol/l (≤45 mg/dl) and <1.7 mmol/l (<30 mg/dl) was higher for hypothermic compared to non-hypothermic neonates (58% vs. 35%, P<.001 and 15% vs. 4%, P=.003).ConclusionHypothermia was strongly associated with neonatal hypoglycemia, leading to more frequent hypoglycemic episodes and a greater need for treatment. Further prospective studies are needed to elucidate the direction of causality between both conditions and to assess the effectiveness of thermal management strategies in reducing hypoglycemia. Awareness should be raised to rule out hypoglycemia in case of hypothermia, and vice versa.